2001
DOI: 10.1111/j.1151-2916.2001.tb01000.x
|View full text |Cite
|
Sign up to set email alerts
|

Conductive Ceramic Foams from Preceramic Polymers

Abstract: Ceramic foams in the system Si-O-C, possessing different bulk densities and morphologies, were obtained from preceramic polymers using two different direct foaming approaches. The electric properties of the foams were varied by adding suitable fillers to the precursor mixtures in amounts up to 80 wt%. The electrical conductivity of the foams was varied by several orders of magnitude. The effects of the type of filler and preceramic polymer (methylsiloxane or methylphenylsiloxane resins), as well as the used fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(57 citation statements)
references
References 7 publications
0
53
0
4
Order By: Relevance
“…[1] A variety of methods have been developed for the fabrication of cellular ceramics, for example, direct foaming techniques based on particle stabilized emulsions, [2][3][4] or preceramic polymer melts. [5][6][7] Nevertheless, ceramic foams for the above mentioned applications are manufactured on an industrial scale by the polymer sponge replication process established by Schwartzwalder and Somers in 1961. [8] This results in a macrocellular foam-like structure similar to that of the polymeric sponge used as template in the process.…”
Section: Introductionmentioning
confidence: 99%
“…[1] A variety of methods have been developed for the fabrication of cellular ceramics, for example, direct foaming techniques based on particle stabilized emulsions, [2][3][4] or preceramic polymer melts. [5][6][7] Nevertheless, ceramic foams for the above mentioned applications are manufactured on an industrial scale by the polymer sponge replication process established by Schwartzwalder and Somers in 1961. [8] This results in a macrocellular foam-like structure similar to that of the polymeric sponge used as template in the process.…”
Section: Introductionmentioning
confidence: 99%
“…The electrical conductivity of polymer-derived porous ceramics depends on the type and amount of fillers and the type of precursor polymers used [85]. A combination of proper selection of the foaming and pyrolysis processes with appropriate fillers is believed to produce porous ceramic structures with a large degree of variation in functionality and properties [6,85,86]. It was also reported that a phenyl methyl poly (silsesquioxane) melt containing small amounts of ethoxy and hydroxyl groups can be foamed by an in situ blowing technique above 200…”
Section: Direct Foamingmentioning
confidence: 99%
“…For example, completely open-celled, interconnected (cell walls containing holes), and closed-cell foams can be obtained using flexible, semi-rigid and rigid PU precursors, respectively [74,75]. On the other hand, the residual carbon content (from PU) can be removed by direct foaming of the preceramic polymer with liquid blowing agent like pentane or Freon, thereby improving high-temperature properties of the foams [6,85]. Microcellular ceramics with a cell size of about 8 µm were fabricated using PMMA microbeads as sacrificial templates [82].…”
Section: Direct Foamingmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7] Depending on the requirements of a given application, microcellular ceramics must exhibit specific cell sizes, cell size distributions, cell morphologies, and different mechanical properties. Obviously, the processing techniques used to develop microcellular ceramics must result in well-controlled microstructures and yield mechanical properties that render the material serviceable for a specific application.…”
Section: 2mentioning
confidence: 99%